Economic aspects of sustainable development of mountain tourism in Montenegro - Knežević Danilo; Knežević Marko (Ekonomski Pogledi, 2014)
The richness and diversity of natural and anthropogenic resources, protected nature and rational management of available funds and monuments are of the essential importance for the sustainable development of mountain tourism in Montenegro. Basic assumptions for such development are represented in the documents; Policy and Strategy for tourism Development in Montenegro till 2020, Strategy for Tourism Development in Montenegro till 2020, and Master Plan till 2020. Sustainable mountain tourism in Montenegro is based on available resources and potentials, regional division, tourist zoning, planning and especially on protected nature and its preservation. Preserved and protected nature as well as cultural Heritage can be successfully valorized through the economic and conversion function. In this area it is more important to improve travel deals by increasing the number and quality of accommodation, by improving of transportation, utility and tourism infrastructure and by solving problems with depositing waste, sewer and pollution of water, soil and air. The aim of this research is to examine the resources and potentials and to emphasize the possibility of their tourist valorization. Thereby, more scientifically proven methods are used (analytical-synthetic, descriptive, causal-explicative, SWOT and Pestel analysis).